Doseresponse effect of black maca (Lepidium meyenii) in mice with memory impairment induced by ethanol - Rubio J. (2011)
The present study was supported by a grant obtained from Peruvian National Council of Sciences, Technology and Innovation (CONCYTEC) through the grant PROCOM 2008. All authors participated in the experimental design and development of the study. Also, the authors report no conflicts of interest. The study was performed in 2008. Since 2009, Dr Gustavo F. Gonzales is in charged of CAYENATUR EIRL an enterprise that develops products based on Maca.